Compatibility of plants application with Islamic values in the Malay landscape of Kota Bharu city / Nur Hafizah Ramle and Nik Ismail Azlan Rahman - Ramle, Nur Hafizah; Azlan Rahman, Nik Ismail (2015)
The research is accomplished to delve the compatibility of Malay landscape between the Islamic values, especially landscape in Kota Bharu city. Islamic religion has expended to Tanah Melayu since long ago had conquered Malay society's culture and surrounding.The characteristic in Islam that can tolerate with many kind of culture make it easily to accept this religion through culture assimilation among Malay society. The occurrence of assimilation of Islamic values has changed many aspect of their way of life either directly or indirectly, including the landscape surrounding. In the proceeding research in Kota Bharu city of Islam which is eagerly developed by Municipality Council of Kota Bharu (Majlis Perbandaran Kota Bharu), the attempt of inserting Islamic landscape motif in the city is under progress.However, this attempt has much or less erode the local Malay landscape.For example, the application of flora species mostly from the Middle East did change the environment of Malay landscape. As such, this research has been undertaken to unearth the compatibility of plants application with islamic value in the malay landscape. Interviews were conducted with few group of respondent to get information and identify people skills with regards to plants and Islam religion. Consequently, identifying functional of plant that compatible with islamic value helps to preserve the Malay landscape and meanwhile protecting the natural heritage and its knowledge.